Female Inmates' Procedural Justice Perceptions of the Police and Courts: Is There a Spill-Over of Police Effects?. (February 2014) - Baker, Thomas; Pelfrey, William V.; Bedard, Laura E.; Dhungana, Karla; Gertz, Marc; Golden, Kristin
Serious offenders, especially incarcerated individuals, are rarely asked to judge the procedural justice of the police and courts. While serious offenders are rarely studied, even more uncommon are assessments of serious female offenders. In addition, despite a fair amount of research on perceptions of the procedural justice of the police and courts, little research has examined the spill-over of police effects onto the perceptions of the courts. This paper aims to bridge these gaps, by examining a sample of female inmates' perceptions of the police and courts, and the spill-over of perceptions of the police onto perceptions of the courts. Results indicate that female offenders' procedural justice perceptions are significantly influenced by their perceived honesty of police officers and the judge, and their perceived opportunity to have their voice heard in police and court encounters. There also appears to be a significant spill-over of police effects onto perceptions about the courts.